An Official Critical Care Societies Collaborative Statement: Burnout Syndrome in Critical Care Healthcare Professionals. Issue 7 (July 2016) - Moss, Marc; Good, Vicki S.; Gozal, David; Kleinpell, Ruth; Sessler, Curtis N.
Abstract : Burnout syndrome (BOS) occurs in all types of healthcare professionals and is especially common in individuals who care for critically ill patients. The development of BOS is related to an imbalance of personal characteristics of the employee and work-related issues or other organizational factors. BOS is associated with many deleterious consequences, including increased rates of job turnover, reduced patient satisfaction, and decreased quality of care. BOS also directly affects the mental health and physical well-being of the many critical care physicians, nurses, and other healthcare professionals who practice worldwide. Until recently, BOS and other psychological disorders in critical care healthcare professionals remained relatively unrecognized. To raise awareness of BOS, the Critical Care Societies Collaborative (CCSC) developed this call to action. The present article reviews the diagnostic criteria, prevalence, causative factors, and consequences of BOS. It also discusses potential interventions that may be used to prevent and treat BOS. Finally, we urge multiple stakeholders to help mitigate the development of BOS in critical care healthcare professionals and diminish the harmful consequences of BOS, both for critical care healthcare professionals and for patients.